(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate Knowledge of Bitewing Radiographs among faculty of public Sector University Karachi, Pakistan. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Jinnah Sindh Medical University (JSMU) and Jinnah Postgraduate Medical Center (JPMC), Karachi during June 2021. Materials and Methods: A questionnaire-based survey was conducted with permission of JSMU Ethical Committee. A questionnaire was disseminated in faculty of the institute. The questionnaire included consent form, demographic details and questions related to bitewing radiographs. Data was analyzed using SPSS version 21. Results: Total 73 complete responses were received and analyzed. Nearly one-third were attending specialization (n=23, 31.5%). All of the participants heard about bitewing radiograph. 41(56.2%) did not prescribe bitewing radiograph in their practice. Majority responded that occlusion radiograph and bitewing radiograph are not the same thing (n=67, 91.8%). Most of the participants were using periapical radiograph n=70, 95.9%) and few reported that were using bitewing (n=2, 2.7%) and occlusal radiograph (n=1, 1.4%). Conclusion: Although dental practitioner had awareness of bitewing radiograph but it is particularly underutilized among practitioners at our institute for diagnosing dental caries. Therefore, trainings sessions should be could conducted to improve the clinical practices to establish appropriate diagnosis of dental caries and providing the timely management to patients.